Establishment and characterization of a novel neuroendocrine carcinoma cell line derived from a human ascending colon tumor. Issue 12 (17th November 2019) - Shinji, Seiichi; Sasaki, Norihiko; Yamada, Takeshi; Koizumi, Michihiro; Ohta, Ryo; Matsuda, Akihisa; Yokoyama, Yasuyuki; Takahashi, Goro; Hotta, Masahiro; Hara, Keisuke; Takeda, Kohki; Ueda, Koji; et al.
Abstract: The incidence of rare neuroendocrine tumors (NET) is rapidly increasing. Neuroendocrine carcinoma (NEC) is a NET with poorly differentiated histological features, high proliferative properties and associated poor prognoses. As these carcinomas are so rare and, thus, affect only a small number of patients allowing for few cell lines to be derived from patient biopsies, the histological, immunohistochemical, and clinical characteristics associated with colorectal NEC and NEC in other organs have yet to be clearly defined. Herein, we describe the establishment of a novel NEC cell line (SS‐2) derived from a tumor resection of the ascending colon from a 59‐year‐old Japanese woman. The histological, electron microscopic and immunohistochemical features of chromogranin A (CgA) as well as confirmation of synaptophysin positivity in this tumor were typical of those commonly observed in surgically resected colorectal NEC. Further, the Ki‐67 labeling index of the resected tumor was >20% and, thus, the tumor was diagnosed as an NEC of the ascending colon. The SS‐2 cell line maintained characteristic features to those of the resected tumor, which were further retained following implantation into subcutaneous tissues of nude mice. Additionally, when SS‐2 cells were seeded into ultra‐low attachment plates, they formed spheres that expressed higher levels of the cancer stem cell (CSC) marker CD133 compared to SS‐2 cells cultured under adherent conditions. SS‐2 cells may, therefore, contribute to the current knowledge on midgut NEC biological function while providing a novel platform for examining the effects of colorectal NEC drugs, including CSC. Abstract : This is the first description of a colorectal NEC cell line established from a tumor of the human ascending colon. Analysis of the present NEC cell line derived from the midgut should clarify the mechanisms of proliferation and metastasis of colorectal NEC and allow tests of antitumor drugs.